Kecernaan Nutrien Domba Fase Akhir Kebuntingan yang Diberi Ransum Flushing dengan Frekuensi yang Berbeda: Nutrient Digestibility of Local Ewes in Late Pregnancy Phase Fed by Flushing Ration with Different Feeding Frequency (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
The aim of this research was to evaluate the nutrient digestibility of late pregnancy local ewes  treated with flushing ration  and different feeding frequency. Twelve local ewes in the late pregnancy phase (BW 49.96 ± 9.67 kg) were divided on a Randomized Block Design with 4 treatments and 3 replications. The treatments were P1 (without flushing), P2 (flushing at the before and after mating), P3 (flushing at the before and after mating, and middle of pregnancy), and P4 (flushing at the before and after mating, middle, and late of pregnancy). Flushing concentrate containing 2% coconut oil and 5% lemuru fish oil. The  variables observed were nutrient consumption and nutrient digestibility. The data were analyzed by using ANOVA, the data with significant differences in the treatment effects were further tested using Duncan Test. The result showed that the treatments significantly affected (p